Manajemen Strategis Pelaksanaan Program Adiwiyata dalam Mewujudkan Tata Kelola Lingkungan yang Baik di SMP Negeri 42 Surabaya - Alvionita Argi Rahmawati; Meirinawati M; Eva Hany Fanida; Trenda Aktiva Oktariyanda (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The Adiwiyata Program is one of the Indonesian government's initiatives aimed at developing environmentally responsible schools through the implementation of Good Environmental Governance principles. The success of the program depends not only on its implementation but also on the school's ability to apply strategic management systematically through strategy formulation, implementation, and evaluation. This study aims to analyze the strategic management of the Adiwiyata Program in achieving good environmental governance at SMP Negeri 42 Surabaya. This research employed a descriptive qualitative approach. Data were collected through observation, interviews, and documentation. The analysis referred to the strategic management theory proposed by Fred R. David and Forest R. David (2017), consisting of strategy formulation, strategy implementation, and strategy evaluation. The findings indicate that strategy formulation includes developing an environmentally oriented vision and mission, conducting internal and external environmental analyses, establishing long-term objectives, and formulating strategic programs. Strategy implementation is carried out through environmentally friendly school policies, integration of environmental education into the curriculum, participatory environmental activities, and the provision of environmentally friendly supporting facilities. Strategy evaluation is conducted through periodic monitoring, performance measurement, and corrective actions. Overall, the strategic management of the Adiwiyata Program at SMP Negeri 42 Surabaya has been implemented effectively and contributes to achieving good environmental governance, although several challenges remain, including uneven student participation, budget limitations, infrastructure optimization, and program sustainability.